Comparative Study of Multiple Regression Model with Curvefit Model for The Prediction of Solar Radiation in Mubi Town Adamawa State, Nigeria - Luqman Raji; Maxwell Francis; A K Issa (Bandung State Polytechnic (Politeknik Negeri Bandung), 2022)
The sun emits solar radiation, which is critical for researchers working on renewable energy technology that provides ecologically favorable power systems. This research created a new model to forecast DHSR for the Mubi metropolitan area in Adamawa State, Nigeria. Data for this study were obtained from the National Aeronautics and Space Administration (NASA) over a 22-year period (2000 – 2021). When DHSR was employed as an output, the requested values were air temperature (Tai) and relative humidity (Rhi). The MATHLAB curve fitting program was used to create the new DHSR mathematical model. The model was validated using five statistical methods in this study: MSE (mean square error); SSE (sum of square errors); RMSE, Chi-square error (X2), and the absolute fraction of variance (R2) are 0.0005, 0.0064, 0.0231, 0.0011kWh/m2/day, and 0.9998, respectively.